2003
DOI: 10.1302/0301-620x.85b1.12665
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in the management of the position of the femoral head during treatment in a spica cast after reduction of hip dislocation in developmental dysplasia of the hip

Abstract: In this prospective study of 18 hips we compared the efficacy of ultrasound with CT in determining the position of the femoral head in a spica cast after closed or open reduction in children with developmental dysplasia of the hip. Ultrasound was performed through the perineal opening of the cast. With a transinguinal approach, the superior ramus of the pubis, the acetabulum, the femoral head and the femoral neck can be depicted in one plane. The CT and ultrasound images were blinded and reviewed by two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 12 publications
(11 reference statements)
0
43
1
3
Order By: Relevance
“…With that probe both hips were imaged simultaneously. In 2003 van Douveren et al [8] described sonography after closed or open reduction in the operating room. Those authors compared sonographic findings to CT, which was performed a few minutes later.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With that probe both hips were imaged simultaneously. In 2003 van Douveren et al [8] described sonography after closed or open reduction in the operating room. Those authors compared sonographic findings to CT, which was performed a few minutes later.…”
Section: Discussionmentioning
confidence: 99%
“…When we implemented transinguinal sonography in our practice we compared the sonographic results with CT scans [8]. The results showed that sonography was sufficient to demonstrate a normal position of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A close collaboration between surgeons and radiologists is necessary in order to optimize the perineal opening to place a US-transducer through a cast [15].…”
Section: In 1997 Mcnally Et Al [4]mentioning
confidence: 99%